Action Research and Collaboration: A New Perspective in Social Research and Language Education (GIST – Education and Learning Research Journal, 2007)
The disconnection between what counts as social research (SR) and what serves society’s needs and interests results in a way of theorizing which, while useful, does not integrate theory and practice; a form of social theory that is not embodied in real lives and does not help non-academic people understand their contexts and practices. This disconnection in SR demands a new epistemology, a new way of knowing and doing research that can meet the everyday needs of people living real-life situations. A dialectical paradigm, researching and knowing from experience through intellectual study, can enable people to 91 rethink social theory as a practical discipline oriented towards social renewal. Within this perspective, action research (AR) can align social research and teaching to social needs because it creates a space for collaborative reflection about the mutual contrast and integration of many kinds of knowledge systems and the shared design of both the goals and the actions aimed at achieving them. Social researchers and language educators could use AR and collaboration to develop legitimate knowledge, promote social change and solve problems, while creating a space for joint reflection and dynamic interaction in language classrooms.